Reduced graphene oxide doped tellurium nanotubes for high performance supercapacitor - Rani, Pinki; Alegaonkar, Ashwini P.; Biswas, Rathindranath; Jewariya, Yogesh; Kanta Haldar, Krishna; Alegaonkar, Prashant S. (Frontiers in Chemistry, 2022)
Supercapacitors have been achieving great interest in energy storage systems for the past couple of decades. Such devices with superior performance, mainly, depending on the material architecture of the electrodes. We report on the preparation of Tellurium nanotubes (Te-tubes diameter ∼100 nm and length ∼700 nm), with variable doping of conducting network reduced graphene oxide (rGO) to fabricate high-performance electrode characteristics of rGO @ Te. The prepared material was characterized using XRD, FTIR, FESEM, and Raman spectroscopy techniques, including Brunauer-Emmett-Teller, Barrett-Joyner-Halenda measurements. FTIR study revealed that 15% rGO @ Te has a wide C-O vibration band at ∼ 1,100–1,300 cm−1, over other compositions. FESEM study shows the Te-tubes dispersion in rGO layers. The EDX study revealed that 15% of the composition has an optimistic concentration of C and O elements. In other compositions, either at lower/higher rGO concentration, an uneven count of C and O is observed. These support efficient charge dynamics to achieve superior ultra-capacitor characteristics, thereby achieving specific capacitance Csp 170 + F/g @ 10 mV/s in a symmetric configuration. The reported values are thirty times higher than pristine Te-tubes (∼5 F/g). This finding suggests that rGO @ Te is a promising candidate for supercapacitor.